2005
DOI: 10.1111/j.1365-2133.2005.06438.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of psoriasis with topical sirolimus: preclinical development and a randomized, double-blind trial

Abstract: Topically applied sirolimus penetrates normal skin and may have some antipsoriatic and immunosuppressive activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
75
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 22 publications
(31 reference statements)
1
75
0
Order By: Relevance
“…Ormerod et al studied the effect of 2.2% sirolimus in patients with chronic psoriasis areas. They observed a significant decrease in the number of proliferating epidermal cells after 6 weeks and after another 6 weeks the drop was 8% [32]. Some other authors have also noted a decrease in the Ki-67 index in the course of systemic psoriasis treatment, e.g.…”
Section: Discussionmentioning
confidence: 90%
“…Ormerod et al studied the effect of 2.2% sirolimus in patients with chronic psoriasis areas. They observed a significant decrease in the number of proliferating epidermal cells after 6 weeks and after another 6 weeks the drop was 8% [32]. Some other authors have also noted a decrease in the Ki-67 index in the course of systemic psoriasis treatment, e.g.…”
Section: Discussionmentioning
confidence: 90%
“…mTOR inhibitors may offer a range of new therapeutic options for psoriasis patients. Clinical trials indicated that rapamycin, the prototypical mTOR inhibitor could significantly reduce the clinical score of psoriasis when treating psoriasis patients (Ormerod et al, 2005;Reitamo et al, 2001). Everolimus, a semisynthetic macrolide and a member of the mTOR inhibitors family, could lead to the resolution of recalcitrant psoriatic manifestations (Frigerio et al, 2007;Wei & Lai, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…1,3 It was found to be active against several strains of yeast and fungi. However, no activity was observed against gram-positive or gram-negative bacteria.…”
mentioning
confidence: 99%